Congenital heart disease in infancy and childhood. (November 2018) - Bellsham-Revell, Hannah; Burch, Michael
Abstract: Congenital heart disease occurs in approximately 8 per 1000 live births. The most common lesion at birth is a ventricular septal defect, but many are small and do not need surgery. Cyanotic heart disease includes Fallot's tetralogy and transposition of the great arteries, which are both amenable to correction in childhood. More complicated cyanotic lesions are treated by separation of the systemic venous flow by a cavopulmonary connection, often referred to as a Fontan circulation. Some genetic syndromes (Marfan's, Noonan's, Williams') are associated with congenital heart disease, as are chromosomal disorders such as Down's and Turner's syndromes. DiGeorge's syndrome (thymic aplasia, hypoparathyroidism, cono-truncal cardiac defect) and velocardiofacial syndrome (palatal abnormalities, heart defects, dysmorphic features) are associated with microdeletions within the q11 region of chromosome 22.